ORM Promotes Skeletal Muscle Glycogen Accumulation via CCR5-Activated AMPK Pathway in Mice - Qin, Zhen; Wan, Jing-Jing; Sun, Yang; Wang, Peng-Yuan; Su, Ding-Feng; Lei, Hong; Liu, Xia (Frontiers in Pharmacology, 2016)
We found previously that acute phase protein orosomucoid reacts to fatigue and activates C-C chemokine receptor type 5 to increase muscle glycogen storage and enhance muscle endurance (Lei et al., 2016). To explore the underlying molecular mechanisms, we investigated the role of AMP-activated protein kinase, a critical fuel sensor in skeletal muscle, in C-C chemokine receptor type 5-mediated orosomucoid action. It was found orosomucoid increased skeletal muscle AMP-activated protein kinase activation in a time- and dose- dependent manner, which was largely prevented by pharmacological blocking or knockout of C-C chemokine receptor type 5. Administration of orosomucoid also significantly increased the de-phosphorylation and activity of muscle glycogen synthase, the rate-limiting enzyme for glycogen synthesis. The effect was largely absent in mice deficient in C-C chemokine receptor type 5 -/- or AMP-activated protein kinase α2-/-, the predominant isoform in skeletal muscle. Moreover, deletion of AMP-activated protein kinase 2 abolished the effect of orosomucoid on fatigue and muscle glycogen. These findings indicate that orosomucoid may promote glycogen storage and enhance muscle function through C-C chemokine receptor type 5-mdiated activation of AMP-activated protein kinase, which in turn activates glycogen synthase and increases muscle glycogen.